3D self-recovery flexible porous conductive material and preparation method and application thereof
By preparing 3D self-recovery flexible porous conductive materials, the problems of poor shape resilience and difficult complex shape preparation of porous sensors under mechanical stress are solved, and the shape memory, conductivity and shape editability of the material are realized, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411834146.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
The existing porous sensors cannot recover under long-term strong and repeated mechanical stresses, resulting in performance deterioration and complex preparation, which cannot meet the shape requirements of different application scenarios.
A 3D self-recovery flexible porous conductive material is used to mix shape memory polymer materials, organic solvents and sacrificial template additives to form shape memory polymer porous substrates, and polymerize on the pore walls through the catalytic action of the catalyst to achieve the recombination of conductive polymers.
The preparation of 3D self-recovery flexible porous conductive materials is realized, with shape memory function, conductive performance and shape editable performance, solving the problems of poor deformation stability of sensors and difficult to prepare complex shapes, and is suitable for a variety of application scenarios.
Smart Images

Figure CN119708611A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of flexible sensor technology, and in particular, relates to a 3D self-recovering flexible porous conductive material and a preparation method and application thereof. Background Art
[0002] A sensor is a detection device that can sense the information being measured and convert the sensed information into electrical signals or other required forms of information output according to certain rules to meet the requirements of information transmission, processing, storage, display, recording and control.
[0003] A sensor generally consists of four parts: a sensitive element, a conversion element, a conversion circuit and an auxiliary power supply. The sensitive element directly senses the measured quantity and outputs a physical quantity signal that has a definite relationship with the measured quantity; the conversion element converts the physical quantity signal output by the sensitive element into an electrical signal; the conversion circuit is responsible for amplifying and modulating the electrical signal output by the conversion element; the conversion element and the conversion circuit generally also require an auxiliary power supply.
[0004] As the application of sensors becomes more and more extensive, the use scenarios of wearable sensors are increasing. Therefore, the requirements for flexibility, breathability, durability, and adaptability to complex shapes are getting higher and higher. 3D flexible porous sensors have good breathability, but when porous sensors are subjected to long-term strong and repeated mechanical stress, the pore structure in the 3D porous material will collapse, resulting in the inability to restore the sensor shape and performance degradation, which seriously affects the performance of the sensor; in addition, different application scenarios have different requirements for the shape of the sensor, but the process of preparing a suitable sensor shape is complicated, which limits the use of the sensor to a certain extent. Summary of the invention
[0005] The purpose of this application is to provide a 3D self-recovering flexible porous conductive material and its preparation method and application, aiming to solve the problem of poor deformation stability of porous sensors in the prior art and the inability to achieve rapid shape editing.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a method for preparing a 3D self-recovering flexible porous conductive material, comprising the following steps:
[0008] The shape memory polymer material, the organic solvent and the sacrificial template additive are mixed and reacted to obtain a shape memory polymer porous substrate;
[0009] placing the shape memory polymer porous substrate in a catalyst solution for immersion treatment to obtain a catalyst-shape memory polymer porous substrate;
[0010] The catalyst-shape memory polymer porous substrate is placed in the monomer vapor containing the prepared conductive polymer to carry out a polymerization reaction to obtain a 3D self-recovering flexible porous conductive material.
[0011] In some embodiments, the shape memory polymer material includes any one of ethylene-vinyl acetate copolymer, polyethylene, polyisoprene, polyester, copolyester, polyamide, copolyamide, polyvinyl alcohol, polyacrylic acid, polyurethane, polylactic acid, polystyrene, and epoxy resin.
[0012] In some embodiments, the organic solvent includes at least one of cyclohexane, isopropanol, glycol ethyl ether acetate, tetrahydrofuran, dimethylformamide, N-methylpyrrolidone, toluene, ethanol xylene, dichloromethane, chloroform, acetone, and dimethyl sulfoxide.
[0013] In some embodiments, the sacrificial template auxiliary agent includes at least one of sodium chloride particles, white sugar particles, and monosodium glutamate particles.
[0014] In some embodiments, the mass ratio of the shape memory polymer material, the organic solvent and the sacrificial template additive is 0.1-2:1-20:1-50.
[0015] In some embodiments, the mixing reaction is carried out by stirring, the stirring speed is 100 rpm to 1000 rpm, and the temperature of the mixing reaction is 25 to 100°C.
[0016] In some embodiments, the concentration of the catalyst solution is 0.01-10 mol / L.
[0017] In some embodiments, the catalyst is selected from at least one of ferric chloride, ammonium persulfate, potassium permanganate, Ziegler-Natta catalyst, titanium chloride, triethylaluminum, aluminum chloride, zirconium chloride, magnesium chloride, aluminum bromide, potassium permanganate, sodium persulfate, ammonium bromide, perchloric acid, hydrogen peroxide, sodium chlorate, nitric acid, silver nitrate, and sodium hypochlorite.
[0018] In some embodiments, the soaking treatment time is 0.1 to 24 hours.
[0019] In some embodiments, the monomers for preparing the conductive polymer include any one of acetylene, aniline, pyrrole, fluorene, carbazole, and thiophene.
[0020] In some embodiments, the polymerization reaction time is 0.1 to 24 hours.
[0021] In the second aspect, the present application provides a 3D self-recovering flexible porous sensor, which is prepared by using a 3D self-recovering flexible porous conductive material as an electrode material, wherein the 3D self-recovering flexible porous conductive material is prepared by the above-mentioned method for preparing the 3D self-recovering flexible porous conductive material.
[0022] In some embodiments, the 3D self-healing flexible porous sensor has triboelectric and piezoresistive dual sensing modes.
[0023] The first aspect of the present application provides a method for preparing a 3D self-recovering flexible porous conductive material. In the preparation method, a shape memory polymer material is used as a basic material, and a sacrificial template additive is added to act. By changing the shape and particle size of the template, a shape memory polymer porous substrate with different pore sizes and different pore shapes can be obtained; a polymerization reaction occurs on the pore wall of the shape memory polymer porous substrate through the catalytic action of the catalyst, and the shape memory polymer porous substrate and the conductive polymer are composited to obtain a 3D self-recovering flexible porous conductive material with shape memory function, conductive properties, and shape editable properties. The preparation method is simple to operate, and the reaction conditions are mild. It does not require the use of large-scale instruments and equipment, and is conducive to wide application.
[0024] The 3D self-recovering flexible porous sensor provided in the second aspect of the present application has shape memory function, conductive properties and shape editable properties because the 3D self-recovering flexible porous conductive material provided above for the 3D self-recovering flexible porous sensor has flexibility, air permeability, shape memory function, shape editable properties, and triboelectric-piezoresistive dual sensing mode; at the same time, in actual application, it can meet the needs of different shapes and simplify the preparation of complex shapes of sensors; it is conducive to wide use in various fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0026] Figure 1 The present invention provides a method for preparing 3D self-recovering flexible porous sensors of different shapes.
[0027] Figure 2 This is an appearance analysis diagram of the shape memory polymer porous substrate EVA sponge and the 3D self-recovering flexible porous conductive material EVA@PPy sponge provided in the embodiments of the present application.
[0028] Figure 3 This is a scanning electron microscope appearance analysis diagram of the shape memory polymer porous substrate EVA sponge and the 3D self-recovering flexible porous conductive material EVA@PPy sponge provided in the embodiments of the present application.
[0029] Figure 4These are the macroscopic and microstructural diagrams of the shape memory change process of the shape memory polymer porous substrate EVA sponge and the 3D self-recovering flexible porous conductive material EVA@PPy sponge provided in the embodiments of the present application.
[0030] Figure 5 This is a conductivity analysis diagram of the 3D self-recovering flexible porous conductive material EVA@PPy sponge provided in an embodiment of the present application.
[0031] Figure 6 This is a triboelectric performance analysis diagram of the 3D self-recovering flexible porous sensor provided in an embodiment of the present application.
[0032] Figure 7 This is a piezoresistive sensing performance analysis diagram of the 3D self-recovering flexible porous sensor provided in an embodiment of the present application.
[0033] Figure 8 This is a performance analysis diagram of a smart insole prepared using a 3D self-recovering flexible porous sensor provided in an embodiment of the present application.
[0034] Fig. 9 This is a performance analysis diagram of a smart joint belt prepared using a 3D self-recovering flexible porous sensor provided in an embodiment of the present application.
[0035] Fig.10 This is a performance analysis diagram of a smart glove prepared using a 3D self-recovering flexible porous sensor provided in an embodiment of the present application. DETAILED DESCRIPTION
[0036] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0037] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0038] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0039] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0040] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0041] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.
[0042] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0043] The first aspect of the embodiment of the present application provides a method for preparing a 3D self-recovering flexible porous material, comprising the following steps:
[0044] S01. The shape memory polymer material, the organic solvent and the sacrificial template additive are mixed and reacted to obtain a shape memory polymer porous substrate;
[0045] S02. The shape memory polymer porous substrate is placed in a catalyst solution for immersion treatment to obtain a catalyst - shape memory polymer porous substrate;
[0046] S03. Place the catalyst-shape memory polymer porous substrate in the monomer vapor containing the conductive polymer to carry out polymerization reaction to obtain a 3D self-recovering flexible porous conductive material.
[0047] The first aspect of the embodiment of the present application provides a method for preparing a 3D self-recovering flexible porous conductive material. In the preparation method, a shape memory polymer material is used as a base material, and a sacrificial template additive is added to act. By changing the shape and particle size of the template, a shape memory polymer porous substrate with different pore sizes and different pore shapes can be obtained; a polymerization reaction occurs on the pore wall of the shape memory polymer porous substrate through the catalytic action of the catalyst, and the shape memory polymer porous substrate and the conductive polymer are composited to obtain a 3D self-recovering flexible porous conductive material with shape memory function, conductive properties, and shape editable properties. The preparation method is simple to operate, and the reaction conditions are mild. It does not require the use of large-scale instruments and equipment, and is conducive to wide application.
[0048] In step S01, a shape memory polymer material, an organic solvent and a sacrificial template additive are mixed and reacted to obtain a polymer porous substrate.
[0049] In some embodiments, the shape memory polymer material includes any one of ethylene-vinyl acetate copolymer (EVA), polyethylene, polyisoprene, polyester, copolyester, polyamide, copolyamide, polyvinyl alcohol, polyacrylic acid, polyurethane, polylactic acid, polystyrene, and epoxy resin. The shape memory polymer material provided is a new type of functional polymer material, which has the characteristics of both plastic and rubber. Under certain conditions, it is given a certain shape (initial state). When the external conditions change, it can change the shape accordingly and fix it (deformation). If the external environment changes again in a specific way and law, they can be reversibly restored to the initial state. At this point, the cycle of "memory initial state-fixing deformation state-restoring initial state" is completed; so that the obtained material has the function of shape memory.
[0050] In some embodiments, the organic solvent includes at least one of cyclohexane, isopropanol, glycol ethyl ether acetate, tetrahydrofuran, dimethylformamide, N-methylpyrrolidone, toluene, ethanol xylene, dichloromethane, chloroform, acetone, and dimethyl sulfoxide. The organic solvent is provided for dissolving the shape memory polymer material.
[0051] In some embodiments, the sacrificial template auxiliary agent includes at least one of sodium chloride, sugar granules, and monosodium glutamate granules. The function of the sacrificial template auxiliary agent is to produce a porous structure in the shape memory polymer material. In some specific embodiments, the sacrificial template auxiliary agent selects a single material for use, and the resulting polymer porous substrate has the same pore size and pore shape. In other specific embodiments, the sacrificial template auxiliary agent selects at least two materials for use, and the resulting polymer porous substrate has pore sizes of different sizes and different pore shapes.
[0052] In some embodiments, the mass ratio of shape memory polymer material, organic solvent and sacrificial template auxiliary agent is 0.1-2:1-20:1-50. Among them, if the amount of shape memory polymer material added is too little, the colloidal solution formed is too dilute, and the sponge finally obtained is too soft and has poor support; if the amount of shape memory polymer material added is too much, it cannot be completely dissolved, resulting in a waste of material. If the amount of sacrificial template auxiliary agent added is too little, too few pores are produced; if the amount of sacrificial template auxiliary agent added is too much, a part of the sacrificial template auxiliary agent cannot be mixed into the colloidal material, resulting in a waste of material. If the amount of organic solvent added is too little, the polymer material cannot be completely dissolved; if the amount of organic solvent added is too much, the colloidal solution formed is too dilute, the sponge obtained is too soft, has poor support, and is not conducive to use.
[0053] In some embodiments, the mixing reaction is carried out by stirring, the stirring speed is 100 rpm to 1000 rpm, and the temperature of the mixing reaction is 25 to 100° C. The mixing reaction is carried out by stirring, which can accelerate the dissolution of the shape memory polymer material, so that the shape memory polymer material is completely dissolved in the organic solvent to form a colloidal liquid. It is also conducive to the uniform mixing of the shape memory polymer material and the sacrificial template additive, ensuring the formation of uniformly distributed pores in the shape memory polymer material.
[0054] The stirring speed is controlled to be 100 rpm to 1000 rpm. If the speed is too low, uneven mixing of the components will result. If the speed is too high, stirring heating will occur easily, affecting the properties of the material. In some embodiments, the stirring speed includes but is not limited to 100 rpm, 200 rpm, 300 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 900 rpm, and 1000 rpm.
[0055] The temperature of the mixed reaction is controlled to be 25 to 100 ° C. If the reaction temperature is too low, the dissolution will be very slow. If the reaction temperature is too high and exceeds the boiling point of the organic solvent, the mixed solution will boil, affecting the reaction process. Therefore, it is necessary to further determine the temperature of the reaction according to the type of organic solvent selected to ensure that the reaction temperature is lower than the boiling point of the organic solvent. In some embodiments, the temperature of the mixed reaction includes but is not limited to 25 ° C, 50 ° C, 55 ° C, 60 ° C, 65 ° C, 70 ° C, 75 ° C, 80 ° C, 90 ° C, and 100 ° C.
[0056] Furthermore, the reactants are mixed to obtain a mixture, and the mixture is transferred to a mold; after the organic solvent is completely volatilized, the mixture is taken out of the mold, and the sacrificial template additive is thoroughly washed with deionized water to finally obtain a shape memory polymer porous substrate.
[0057] In some embodiments, in this step, the shape memory polymer material and the organic solvent are first mixed to form a colloidal liquid, and then a sacrificial template additive is added for mixing; the mixture is then transferred to a mold, and after the organic solvent is completely evaporated, the mixture is taken out of the mold, and the sacrificial template additive is thoroughly washed with deionized water to obtain a shape memory polymer porous substrate.
[0058] In step S02, the polymer porous substrate is placed in a catalyst solution for immersion treatment to obtain a catalyst-shape memory polymer porous substrate. The shape memory polymer porous substrate is saturated with the catalyst solution to promote the subsequent polymerization reaction. During the immersion treatment, the catalyst solution will not react with the shape memory polymer porous substrate.
[0059] In some embodiments, the concentration of the catalyst solution is 0.01 to 10 mol / L. If the concentration of the catalyst solution is too high or too low, the catalytic rate of the reaction will be affected. In some specific embodiments, the concentration of the catalyst solution includes but is not limited to 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 2.0 mol / L, 3.0 mol / L, 4.0 mol / L, 5.0 mol / L, 6.0 mol / L, 7.0 mol / L, 8.0 mol / L, 9.0 mol / L, 10.0 mol / L.
[0060] In some embodiments, the catalyst is selected from at least one of ferric chloride, ammonium persulfate, potassium permanganate, Ziegler-Natta catalyst, titanium chloride, triethylaluminum, aluminum chloride, zirconium chloride, magnesium chloride, aluminum bromide, potassium permanganate, sodium persulfate, ammonium bromide, perchloric acid, hydrogen peroxide, sodium chlorate, nitric acid, silver nitrate, and sodium hypochlorite.
[0061] During specific use, the type of catalyst is determined according to the material of the monomer selected for preparing the conductive polymer. In some specific embodiments, when the monomer for preparing the conductive polymer is selected from pyrrole, the catalyst is selected from any one of ferric chloride, ammonium persulfate, potassium permanganate, hydrogen peroxide, silver nitrate, and sodium hypochlorite; when the monomer for preparing the conductive polymer is selected from acetylene, the catalyst is selected from any one of Ziegler-Natta catalyst, titanium chloride, triethylaluminum, aluminum chloride, zirconium chloride, organic metal compounds, magnesium chloride, aluminum bromide, and potassium permanganate; when the monomer for preparing the conductive polymer is selected from aniline, the catalyst is selected from any one of ammonium persulfate, ferric chloride, hydrogen peroxide, sodium chlorate, potassium permanganate, nitrate, etc. any one of acid, sodium persulfate, and ammonium bromide; when the monomer for preparing the conductive polymer is selected from thiophene, the catalyst is selected from any one of ferric chloride, ammonium persulfate, perchloric acid, hydrogen peroxide, sodium chlorate, ammonium bromide, and sodium persulfate; when the monomer for preparing the conductive polymer is selected from fluorene, the catalyst is selected from any one of ferric chloride, ammonium persulfate, perchloric acid, sodium persulfate, hydrogen peroxide, sodium chlorate, ammonium bromide, and potassium permanganate; when the monomer for preparing the conductive polymer is selected from carbazole, the catalyst is selected from any one of ferric chloride, ammonium persulfate, hydrogen peroxide, aluminum chloride, and cupric chloride.
[0062] In some embodiments, the soaking treatment time is 0.1 to 24 hours. The soaking treatment time is ensured to be appropriate so that the catalyst can be fully loaded on the shape memory polymer porous substrate.
[0063] In step S03, the catalyst-shape memory polymer porous substrate is placed in the monomer vapor containing the conductive polymer to carry out polymerization reaction to obtain a 3D self-recovering flexible porous conductive material.
[0064] In some embodiments, a vacuum drying oven is provided, and the vacuum drying oven is evacuated to provide vacuum conditions; the purpose of providing vacuum conditions is to accelerate the evaporation of monomers for preparing conductive polymers, so that polymerization reaction occurs on the pore walls of the shape memory polymer porous substrate through the catalytic action of the catalyst to form conductive polymers, thereby achieving the composite of the shape memory polymer porous substrate and the conductive polymer.
[0065] In some embodiments, the monomers for preparing the conductive polymer include any one of acetylene, aniline, pyrrole, fluorene, carbazole and thiophene. The provided monomers are subjected to polymerization reaction to obtain a conductive polymer, and the resulting conductive polymer can exhibit good conductivity and stability. Among them, the acetylene monomer has high chemical activity and is prone to addition reaction, and the polyacetylene obtained by polymerization has good conductivity. The polyaniline obtained by the polymerization reaction of aniline monomer has high electrical conductivity and environmental stability. The polypyrrole obtained by the polymerization reaction of pyrrole also has the characteristics of excellent conductive properties. The polyfluorene obtained by the polymerization reaction of fluorene is a polymer material with good photoelectric properties, thermal stability and mechanical properties. The polycarbazole obtained by the polymerization reaction of carbazole has good electron transport properties and thermal stability. The polythiophene obtained by the polymerization reaction of thiophene is a common conductive polymer with excellent conductivity and optical properties. In the polymerization process of the monomer material, it is usually necessary to use a specific catalyst and reaction conditions to ensure the smooth progress of the polymerization reaction and the stable performance of the material. Therefore, in the specific reaction process, it is necessary to determine the choice of catalyst according to the type of the selected monomer. In some embodiments, the polymerization reaction time is 0.1 to 24 hours. In some specific embodiments, the polymerization reaction time includes but is not limited to 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 17 hours, 19 hours, 21 hours, and 24 hours.
[0066] Furthermore, after the polymerization reaction, the mixture is washed with deionized water to remove unreacted reagents and impurities, and then naturally dried at room temperature.
[0067] The second aspect of an embodiment of the present application provides a 3D self-recovering flexible porous sensor, which is prepared by using a 3D self-recovering flexible porous conductive material, wherein the 3D self-recovering flexible porous conductive material is prepared by the above-mentioned method for preparing the 3D self-recovering flexible porous conductive material.
[0068] The 3D self-recovering flexible porous sensor provided in the second aspect of the embodiment of the present application has the shape memory function, conductive properties and shape editable properties of the 3D self-recovering flexible porous conductive material provided above for the 3D self-recovering flexible porous sensor; therefore, the obtained 3D self-recovering flexible porous sensor has flexibility, air permeability, shape memory function, shape editable properties, and triboelectric-piezoresistive dual sensing mode; at the same time, in the actual application process, it can meet the needs of different shapes and simplify the preparation of complex shapes of sensors; it is conducive to wide use in various fields.
[0069] A shape-editable 3D self-recovering flexible porous sensor with shape memory function is prepared. When the pore structure of the 3D porous material collapses, it is restored to its original shape by applying external stimulation (such as heat stimulation, electrical stimulation, light stimulation, humidity stimulation, pH stimulation, magnetic field stimulation, chemical stimulation, mechanical stimulation) to ensure the performance of the sensor. To prepare the sensor, the porous material must have conductive properties. A writable gas phase polymerization technology has been developed to polymerize on the pore walls of the non-conductive 3D self-recovering flexible porous material to form a conductive polymer film, giving the 3D self-recovering flexible porous material conductive properties. And by writing, the desired sensor shape can be flexibly obtained on the non-conductive 3D self-recovering flexible porous material, meeting the needs of practical applications for different shapes and simplifying the preparation of complex sensor shapes.
[0070] In some embodiments, the 3D self-recovering flexible porous sensor has a triboelectric sensing mode and a piezoresistive sensing mode. The triboelectric sensing mode has the following mechanism: when the 3D self-recovering flexible porous conductive material contacts other materials, an electrical signal is generated based on the principles of frictional electrification and electrostatic induction, and the detected behavior change is determined based on the electrical signal. The piezoresistive sensing mode has the following mechanism: the deformation of the 3D self-recovering porous conductive material will cause a change in internal resistance, and the detected behavior change is obtained through the change in internal resistance.
[0071] Furthermore, the obtained 3D self-recovering flexible porous sensor is widely used in the fields of smart insoles, smart joint belts, smart gloves, and coastal structure materials. In some specific embodiments, the 3D self-recovering flexible porous sensor is used to prepare smart insoles, which can be used to detect the pressure distribution of the foot during human activities; the 3D self-recovering flexible porous sensor is used to prepare smart joint belts, which can be used to detect the movement of human joints and the movement of different positions of the same joint; the 3D self-recovering flexible porous sensor is used to prepare smart gloves, which can be used to detect the pressure distribution of the palm when the hand grasps an object, perform object recognition when in contact with objects of different properties, detect the rehabilitation training of the human hand, detect the movement of the finger joints, send Morse code, and have the potential to realize human-computer interaction; the 3D self-recovering flexible porous sensor is used to prepare the surface material of the coastal structure, which has the potential to collect wave energy and buffer the stress damage caused by waves to the structure.
[0072] The following describes the invention in conjunction with specific embodiments.
[0073] Example 1
[0074] 3D self-recovering flexible porous conductive material and preparation method thereof
[0075] A method for preparing a 3D flexible porous conductive material comprises the following steps:
[0076] The shape memory polymer material ethylene-vinyl acetate copolymer and the organic solvent cyclohexane are mixed in a mass ratio of 1:5, and stirred at a speed of 600 rpm at 65°C. After the shape memory polymer material ethylene-vinyl acetate copolymer is dissolved in the organic solvent cyclohexane to form a colloidal liquid, a sacrificial template auxiliary agent sodium chloride is added, and the sodium chloride is evenly dispersed in the colloidal liquid by stirring. The mass ratio of ethylene-vinyl acetate copolymer, cyclohexane and sodium chloride is 1:5:22, and then the mixture is transferred to a mold. After the organic solvent cyclohexane is completely volatilized, the mixture is taken out from the mold, and the sacrificial template auxiliary agent sodium chloride is thoroughly washed with deionized water to obtain a shape memory polymer porous substrate;
[0077] The shape memory polymer porous substrate is placed in a catalyst ferric chloride solution with a concentration of 0.1 mol / L and immersed for 1 hour to obtain a catalyst-shape memory polymer porous substrate;
[0078] The catalyst-shape memory polymer porous substrate and the culture dish containing pyrrole were placed in a vacuum drying oven together. The vacuum drying oven was evacuated using a vacuum pump to produce a negative pressure condition of -0.1 mPa. The gas phase polymerization reaction was carried out for 1 hour. The final porous material was washed with deionized water to remove unreacted reagents and impurities. Finally, it was naturally dried at room temperature to obtain a 3D self-recovering flexible porous conductive material.
[0079] Example 2
[0080] 3D self-recovering flexible porous conductive material and preparation method thereof
[0081] A method for preparing a 3D self-recovering flexible porous conductive material comprises the following steps:
[0082] The shape memory polymer material polyamide is mixed with the organic solvent toluene, and stirred at 65°C and 600 rpm. After the shape memory polymer material polyamide is dissolved, a sacrificial template auxiliary agent sodium chloride is added, and the sodium chloride is evenly dispersed therein by stirring. Then, the mixture is transferred to a mold. After the organic solvent toluene is completely volatilized, the mixture is taken out from the mold, and the sacrificial template auxiliary agent sodium chloride is thoroughly washed with deionized water to obtain a shape memory polymer porous substrate.
[0083] The shape memory polymer porous substrate is placed in a catalyst Ziegler-Natta catalyst solution for immersion treatment for 1 to 4 hours to obtain a catalyst-shape memory polymer porous substrate;
[0084] At room temperature and normal pressure, acetylene gas is provided, and the catalyst-polymer porous substrate is placed in an acetylene gas environment to carry out polymerization reaction for several hours. The final porous material is washed with deionized water to remove unreacted reagents and impurities, and finally dried naturally at room temperature to obtain a 3D self-recovering flexible porous conductive material.
[0085] Example 3
[0086] 3D porous flexible material and preparation method thereof
[0087] The preparation method of 3D porous flexible material comprises the following steps:
[0088] The shape memory polymer material polyurethane is mixed with the organic solvent isopropanol, and stirred at 60°C and 600rpm. After the shape memory polymer material polyurethane is dissolved, sugar particles as a sacrificial template auxiliary are added, and the sugar particles are evenly dispersed therein by stirring. Then, the mixture is transferred to a mold. After the organic solvent isopropanol is completely volatilized, the mixture is taken out from the mold, and the sugar particles as the sacrificial template auxiliary are thoroughly washed with deionized water to obtain a shape memory polymer porous substrate.
[0089] The shape memory polymer porous substrate is placed in a catalyst ammonium persulfate solution with a concentration of 0.2 to 0.5 mol / L for immersion treatment for 1 to 4 hours to obtain a catalyst-shape memory polymer porous substrate;
[0090] At room temperature and pressure, a culture dish containing aniline is provided, and a catalyst-shape memory polymer porous substrate is placed in a vapor environment containing aniline to carry out a polymerization reaction for 4 to 12 hours. The final porous material is washed with deionized water to remove unreacted reagents and impurities, and finally dried naturally at room temperature to obtain a 3D self-recovering flexible porous conductive material.
[0091] Example 4
[0092] 3D porous flexible material and preparation method thereof
[0093] The preparation method of 3D porous flexible material comprises the following steps:
[0094] The shape memory polymer material polyisoprene is mixed with the organic solvent cyclohexane, and stirred at 50°C and 600 rpm. After the shape memory polymer material polyisoprene is dissolved, sacrificial template auxiliary monosodium glutamate particles are added, and the monosodium glutamate particles are uniformly dispersed therein by stirring. Then, the mixture is transferred to a mold. After the organic solvent cyclohexane is completely volatilized, the mixture is taken out from the mold, and the sacrificial template auxiliary monosodium glutamate particles are thoroughly washed with deionized water to obtain a shape memory polymer porous substrate.
[0095] The shape memory polymer porous substrate is placed in a catalyst ferric chloride solution with a concentration of 0.5 mol / L for immersion treatment for 1 to 4 hours to obtain a catalyst-shape memory polymer porous substrate;
[0096] A culture dish containing thiophene is provided at room temperature and pressure, and a catalyst-polymer porous substrate is placed in a vapor environment containing thiophene to carry out a polymerization reaction for 4 to 12 hours. The final porous material is washed with deionized water to remove unreacted reagents and impurities, and finally dried naturally at room temperature to obtain a 3D self-recovering flexible porous conductive material.
[0097] Example 5
[0098] Fabrication of sensors of different shapes
[0099] According to the raw material ratios and preparation method of the 3D self-recovering flexible porous conductive material provided in Example 1, sensors of different shapes can be obtained by a template method or a writing method.
[0100] The template method is used to obtain sensors of different shapes. The specific steps are as follows:
[0101] A shape memory polymer porous substrate is prepared according to the method of Example 1, a hollow template with a desired shape is placed on the top of the shape memory polymer porous substrate ethylene-vinyl acetate copolymer (EVA) sponge, and then a catalyst ferric chloride (FeCl3) solution is added to the hollow pattern of the template; and then it is placed in a vacuum desiccator together with a culture dish containing pyrrole (Py) solution and placed under vacuum conditions to perform a gas phase polymerization reaction, and the desired polypyrrole (PPy) shape is obtained on the EVA sponge, thereby obtaining sensors of different shapes (such as Figure 1 a~e).
[0102] The writing method is used to obtain sensors of different shapes. The specific steps are as follows:
[0103] A shape memory polymer porous substrate was prepared according to the method of Example 1. A pen containing a Py solution was used to draw a desired shape on the shape memory polymer substrate EVA sponge, and then another pen containing a FeCl3 solution was used to trace the drawn shape to obtain sensors of different shapes (such as Figure 1 a and f).
[0104] Performance testing and result analysis
[0105] (i) The shape memory polymer porous substrate EVA sponge and the 3D self-recovering flexible porous conductive material EVA@PPy sponge obtained in Example 1 were subjected to appearance analysis and scanning electron microscope appearance analysis respectively.
[0106] The appearance analysis of shape memory polymer porous substrate EVA sponge and 3D self-recovering flexible porous conductive material EVA@PPy sponge is shown in the attached figure. Figure 2 As shown, Figure 2 a, b, and c are all shape memory polymer porous substrate EVA sponges. It can be seen that the shape memory polymer porous substrate EVA sponge is a flexible porous material with very light weight; Figure 2 Figures d, e, and f are all 3D self-recovering flexible porous conductive material EVA@PPy sponge. It can be seen that the 3D self-recovering flexible porous conductive material EVA@PPy sponge is a flexible porous material with very light weight.
[0107] The scanning electron microscope appearance analysis of the shape memory polymer porous substrate EVA sponge and the 3D self-recovering flexible porous conductive material EVA@PPy sponge is shown in the attached figure. Figure 3 As shown, Figure 3 a is a scanning electron microscope microscopic image of the shape memory polymer porous substrate EVA sponge. Figure 3 b is a scanning electron microscope microscopic image of the pore wall of the shape memory polymer porous substrate EVA sponge. Figure 3 c is a scanning electron microscope microscopic image of the 3D self-recovering flexible porous conductive material EVA@PPy sponge. Figure 3 Figure d is a scanning electron microscope microscopic morphology of the pore wall of the 3D self-recovering flexible porous conductive material EVA@PPy sponge, where the PPy film on the surface of the pore wall can be seen.
[0108] (ii) The shape memory polymer porous substrate EVA sponge and the 3D self-recovering flexible porous conductive material EVA@PPy sponge obtained in Example 1 were subjected to shape memory testing.
[0109] Test method: The shape memory effect of the prepared shape memory polymer porous substrate EVA sponge and the 3D self-recovering flexible porous conductive material EVA@PPy sponge was evaluated by compression deformation. The sample was placed in a blast drying oven at 65°C (the glass transition temperature (Tg) of EVA). After 5 minutes, the sample was squeezed into an M shape using an M-shaped mold. After keeping it for 5 minutes, the sample was naturally cooled to room temperature and the first stage sample condition was observed. The sample was then placed back in the drying oven at 65°C to observe the second stage sample condition.
[0110] like Figure 4 As shown, Figure 4 a is a macroscopic diagram of the shape memory change process of the shape memory polymer porous substrate EVA sponge. Figure 4 b is the microstructure diagram of the shape memory change process of the shape memory polymer porous substrate EVA sponge. Figure 4 c is a macroscopic diagram of the shape memory change process of the 3D self-recovering flexible porous conductive material EVA@PPy sponge. Figure 4 Figure d is a microstructure diagram of the shape memory change process of the 3D self-recovering flexible porous conductive material EVA@PPy sponge. It can be seen that the shape memory polymer porous substrate EVA sponge and the 3D self-recovering flexible porous conductive material EVA@PPy sponge will maintain an M-shaped structure in the first stage; in the second stage, the sample will return to its original rectangular shape.
[0111] (III) Conductivity test of the 3D self-recovering flexible porous conductive material EVA@PPy sponge obtained in Example 1.
[0112] Test method: Use a multimeter to connect the 3D self-recovering flexible porous conductive material EVA@PPy sponge with electrodes at both ends and check the multimeter display. In addition, use a digital source meter to further analyze the conductivity of the 3D self-recovering flexible porous conductive material EVA@PPy sponge obtained at different gas phase polymerization times.
[0113] like Figure 5 As shown, Figure 5 The a is that the two electrodes of the multimeter are not connected through the 3D self-recovery flexible porous conductive material EVA@PPy sponge, and the multimeter does not display a value. Figure 5 b is that the two electrodes of the multimeter are connected through the 3D self-recovery flexible porous conductive material EVA@PPy sponge, and the multimeter displays a value, indicating that the 3D self-recovery flexible porous conductive material EVA@PPy sponge has conductivity; Figure 5 Figure c is an analysis chart of the electrical conductivity of the 3D self-recovering flexible porous conductive material EVA@PPy sponge and the gas phase polymerization time. It can be seen that with the increase of the gas phase polymerization time, the electrical conductivity of the material will also increase, showing a positive correlation.
[0114] (iv) The 3D self-recovering flexible porous conductive material EVA@PPy sponge obtained in Example 1 was used to prepare a 3D self-recovering flexible porous sensor, and the triboelectric properties of the 3D self-recovering flexible porous sensor were further analyzed.
[0115] Triboelectric performance test method: A linear motor is used to drive a triboelectric nanogenerator based on 3D self-healing flexible porous conductive material EVA@PPy sponge. The triboelectric nanogenerator is connected to an oscilloscope, current amplifier and electrometer through wires. The oscilloscope, current amplifier and electrometer are used to record the open circuit voltage, short circuit current and transferred charge generated by the triboelectric nanogenerator. The triboelectric output performance is determined by analyzing the open circuit voltage, short circuit current and transferred charge.
[0116] The results are as follows Figure 6 As shown, the details are as follows: Figure 6As shown in a, when the 3D self-healing flexible porous conductive material EVA@PPy sponge comes into contact with other materials, due to the different electronegativity, the two surfaces will carry different charges, resulting in a potential difference between the two. Under the action of the potential difference, electrons generate electrical signals through the external circuit, which is the principle of triboelectricity. Figure 6 As shown in figure b, the open circuit voltages generated by the interaction with materials of different electronegativity are different. The interaction with materials that are easy to gain electrons produces obvious open circuit voltage signals, while the interaction with materials that are easy to lose electrons produces almost no open circuit voltage signals, indicating that the 3D self-healing flexible porous conductive material EVA@PPy sponge is easy to lose electrons. Figure 6 As shown in ce, the friction nanogenerator prepared using 3D self-recovering flexible porous conductive material EVA@PPy sponge has stable short-circuit current, open-circuit voltage and transferred charge output.
[0117] The peak power density of the triboelectric nanogenerator based on 3D self-recovering flexible porous conductive materials was measured by connecting different external load resistors. Figure 6 As shown in f and g, as the external resistance increases from 39 kΩ to 10 GΩ, the output voltage increases and the output current decreases. Subsequently, the maximum peak power density of the triboelectric nanogenerator is 7.8 mVm at 60 MΩ. -2 .like Figure 6 As shown in h, the friction nanogenerator based on the 3D self-recovering flexible porous conductive material EVA@PPy sponge can maintain stable output after 10,000 cycles, indicating that it has long-term output stability.
[0118] (V) The 3D self-recovering flexible porous conductive material EVA@PPy sponge obtained in Example 1 was used to prepare a 3D self-recovering flexible porous sensor, and the piezoresistive properties of the 3D self-recovering flexible porous sensor were further analyzed.
[0119] Piezoresistive performance test method: Connect the sensor to the digital source meter through wires, and use the digital source meter to detect the resistance change during the deformation of the EVA@PPy sponge. The piezoresistive sensing performance is determined by analyzing the change in the value of (real-time resistance-initial resistance) / initial resistance, that is, ΔR / R0.
[0120] The results are as follows Figure 7 As shown in the figure, specifically: the sensor based on the 3D self-recovering flexible porous conductive material EVA@PPy sponge exhibits a piezoresistive sensing effect when detecting pressure stimulation. Figure 7As shown in a, under the action of external force, the resistance of the 3D self-recovering flexible porous conductive material EVA@PPy sponge first increases sharply and then gradually decreases, indicating that the resistance first increases and then decreases during the compression process, causing the ΔR / R0 value to fluctuate around zero. After the external pressure is removed, the resistance increases instantaneously and then returns to the initial value. The initial increase in resistance is due to the instantaneous horizontal stretching of the 3D self-recovering flexible porous conductive material EVA@PPy sponge during the compression process, while the decrease in resistance is due to the collapse of the porous structure, which enhances connectivity and increases conductivity. After the external force is removed, the resistance returns to its initial value as the porous structure returns to its original state. In addition, response time is an important parameter for evaluating piezoresistive sensing performance. The response time of the piezoresistive sensor based on the 3D self-recovering flexible porous conductive material EVA@PPy sponge is only 150ms under a pressure of 20N, indicating that the sensor can respond quickly to external forces. As shown in Figure 7 As shown in Figure b, as the external force increases from 0 to 100 N, the conductivity gradually increases. This is due to the collapse of the porous structure during the extrusion process, which leads to enhanced connectivity and reduced resistance. Figure 7 As shown in Figure c, when the compression rate remains unchanged, the ΔR / R0 value remains stable after 3000 compression deformation cycles, confirming that the sensor based on the 3D self-recovering flexible porous conductive material EVA@PPy sponge has stable electromechanical properties in the piezoresistive mode.
[0121] (six) The 3D self-recovering flexible porous conductive material EVA@PPy sponge obtained in Example 1 is used to prepare a 3D self-recovering flexible porous sensor, and the obtained 3D self-recovering flexible porous sensor is prepared into a smart insole, and performance testing and analysis are performed.
[0122] Specific testing method: Connect the sensor on the smart insole and the oscilloscope through a wire, use the oscilloscope to record the open circuit voltage signal caused by the interaction between the sole and the insole during human activities, and use this to determine the pressure distribution on the sole during human activities.
[0123] The results are as follows Figure 8 As shown in the figure, the integrated smart insole based on triboelectric sensing is used to detect the pressure distribution of the sole of the foot during human activities. Since the triboelectric sensor array is formed on the surface of the shape memory polymer porous substrate EVA sponge through the polypyrrole reaction at the same time, the formed sensor has a high degree of consistency. Figure 8 As shown in a, according to the distribution of foot pressure, 38 triboelectric sensors with a diameter of 18 mm are arranged in a non-matrix form at the toes, soles, arches and heels. The pressure distribution on the soles of volunteers wearing smart insoles when crossing obstacles was studied. Figure 8As shown in Figure b, during the process of crossing the obstacle, the volunteer's right foot went through six different states: (i) standing, (ii) lifting the foot, (iii) leaving the ground, (iv) crossing the obstacle, (v) landing, and (vi) leaving. The digital camera captured the six key moments in this process. When the volunteer's right foot came into contact with and left the ground, the sensor based on the triboelectric sensing mechanism on the smart insole generated an electrical signal to reflect the state of movement. The smart insole continuously monitored the pressure changes of the right foot throughout the process of crossing the obstacle. Figure 8 Figure c shows the open circuit voltage curves of the sensor array on the smart insole when the volunteers crossed the obstacle. These open circuit voltage curves show peaks and troughs corresponding to the six states. The peaks represent the release of pressure from the foot leaving the insole, while the troughs correspond to the pressure applied by the foot to the insole. The experimental results show that Figure 8 As shown in d, each sensor of the smart insole can independently record the dynamic changes of the sole pressure at the sensor. The sole pressure distribution can be obtained based on the electrical signals of all sensors on the insole.
[0124] (VII) The 3D self-recovering flexible porous conductive material EVA@PPy sponge obtained in Example 1 is used to prepare a 3D self-recovering flexible porous sensor, and the obtained 3D self-recovering flexible porous sensor is prepared into a smart joint belt, and performance testing and analysis are performed.
[0125] Specific testing method: Connect the sensor and digital source meter on the smart joint belt through wires, use the digital source meter to record the piezoresistive signal generated during the operation of the smart joint belt, and use it to judge the activity of the joint.
[0126] The results are as follows Fig. 9 As shown, it is specifically a smart joint belt based on 3D self-recovering flexible porous conductive material EVA@PPy sponge, such as Fig. 9 As shown in a. It is used to monitor the movement of human joints, including finger bending, wrist bending, elbow bending and knee bending. The 3D self-recovering flexible porous conductive material EVA@PPy sponge is soft and comfortable, breathable, fits human skin, and can also provide protection for joints. When the joints bend, the 3D self-recovering flexible porous conductive material EVA@PPy sponge also deforms accordingly, causing its internal resistance to change. Fig. 9 As shown in Figure b, as the finger bending angle increases from 30 degrees to 60 degrees and then to 90 degrees, the peak value of the sensor's ΔR / R0 gradually increases negatively. Therefore, the degree of finger bending can be evaluated based on the peak signal. Similar patterns also appear in sensors worn on the wrist, elbow, and knee, such as Fig. 9The piezoresistive sensor based on the 3D self-recovering flexible porous conductive material EVA@PPy sponge exhibits stable and repeatable characteristics in all joint activities, verifying its feasibility as a sensor for detecting human joint activities. In addition, each joint belt contains multiple sensors, allowing for simultaneous detection of multiple positions on the same joint, thus addressing the gap in detecting multiple position movements on a single joint. Fig. 9 As shown in dg, the medial and lateral movements of the elbow and knee joints can be recorded simultaneously. Therefore, the distribution of movement of different parts of the same joint can be shown, such as Fig. 9 By detecting the pressure distribution on the soles of the feet and the movement distribution of the joints during human activities, all-round human body detection can be achieved, such as Fig. 9 As shown in i.
[0127] (VIII) The 3D flexible porous conductive material EVA@PPy sponge obtained in Example 1 is used to prepare a 3D flexible porous sensor, and the obtained 3D flexible porous sensor is prepared into a smart glove, and performance testing and analysis are performed.
[0128] The specific test method is to connect the sensor on the smart glove with an oscilloscope and a digital source meter, and use the oscilloscope and the digital source meter to record the triboelectric and piezoresistive signals generated by the smart glove during hand movement. This can be used to determine the smart glove's recognition of different objects; the pressure distribution of the palm when grasping an object; sending Morse code; and real-time detection of hand rehabilitation training.
[0129] The results are as follows Fig.10 As shown, the smart gloves with triboelectric-piezoresistive dual sensing modes are constructed, such as Fig.10 The sensor on the palm of the glove is based on the triboelectric sensing mode, which enables it to identify different objects, detect the pressure distribution of the palm when grasping objects, and send Morse code. When the glove is applied to the hands of humans or robots, the glove will have different open circuit voltage outputs when it comes into contact with different materials. Fig.10 As shown in b, the output open circuit voltage signal is the strongest when in contact with PTFE, while the output open circuit voltage signals are weakened in turn when in contact with PDMS, FEP, PMMA, PET, Cu, and Al. During the contact-separation process, the greater the difference in electronegativity between the external material and the 3D self-recovering flexible porous conductive material EVA@PPy sponge, the more obvious the output open circuit voltage signal. Therefore, when smart gloves are applied to human hands, smart manipulators or prostheses, human hands, smart manipulators or prostheses can recognize different materials. In addition, since the sensor array is prepared on the shape memory polymer porous substrate EVA sponge through gas phase polymerization reaction at the same time, the sensor array has a high consistency, and the palm pressure distribution during grasping objects can be comprehensively detected based on the electrical signal strength of the sensor array, such as Fig.10 In addition, when sending Morse code, the short point signal "·" and the long point signal "-" can be replaced by a single pulse and a double pulse respectively, as shown in Fig.10 In this way, the Morse code can be displayed through the friction electric signal, thereby simulating and identifying signals similar to "NANO", such as Fig.10 The sensor on the back of the glove is based on the piezoresistive sensing mode and can detect hand rehabilitation training in real time, such as Fig.10 As shown in i, it shows its potential application in patient rehabilitation training monitoring.
[0130] In summary, the preparation method of the 3D self-recovering flexible porous conductive material provided in the embodiment of the present application uses a shape memory polymer material as the base material, and then adds a sacrificial template additive to act, and obtains a shape memory polymer porous substrate with different pore sizes and different pore shapes by changing the shape and particle size of the template; a polymerization reaction occurs on the pore wall of the shape memory polymer porous substrate through the catalytic action of the catalyst, and the composite of the shape memory polymer porous substrate and the conductive polymer is realized to obtain a 3D self-recovering flexible porous conductive material with flexibility, air permeability, shape memory function, conductivity, and shape editable performance. The preparation method is simple to operate, and the reaction conditions are mild. It does not require the use of large-scale instruments and equipment, and is conducive to wide application.
[0131] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a 3D self-recovering flexible porous conductive material, characterized in that: The steps include: The shape memory polymer material, the organic solvent and the sacrificial template additive are mixed and reacted to obtain a shape memory polymer porous substrate; placing the shape memory polymer porous substrate in a catalyst solution for immersion treatment to obtain a catalyst-shape memory polymer porous substrate; The catalyst-shape memory polymer porous substrate is placed in monomer vapor containing a conductive polymer for preparation, and a polymerization reaction is carried out to obtain a 3D self-recovering flexible porous conductive material.
2. The method for preparing a 3D self-recovering flexible porous conductive material according to claim 1, characterized in that: The shape memory polymer material includes any one of ethylene-vinyl acetate copolymer, polyethylene, polyisoprene, polyester, copolyester, polyamide, copolyamide, polyvinyl alcohol, polyacrylic acid, polyurethane, polylactic acid, polystyrene, and epoxy resin; and / or, The organic solvent includes at least one of cyclohexane, isopropanol, glycol ethyl ether acetate, tetrahydrofuran, dimethylformamide, N-methylpyrrolidone, toluene, ethanol, xylene, dichloromethane, chloroform, acetone, and dimethyl sulfoxide, and / or, The sacrificial template auxiliary agent includes at least one of sodium chloride, white sugar granules, and monosodium glutamate granules.
3. The method for preparing the 3D self-recovering flexible porous conductive material according to claim 1, characterized in that: The mass ratio of the shape memory polymer material, the organic solvent and the sacrificial template auxiliary agent is 0.1-2:1-20:1-50.
4. The method for preparing a 3D self-recovering flexible porous conductive material according to claim 1, characterized in that: The mixing reaction is carried out by stirring, the stirring speed is 100 rpm to 1000 rpm, and the temperature of the mixing reaction is 25 to 100°C.
5. The method for preparing a 3D self-recovering flexible porous conductive material according to any one of claims 1 to 4, characterized in that: The concentration of the catalyst solution is 0.01 to 10 mol / L; and / or, The catalyst is selected from at least one of ferric chloride, ammonium persulfate, potassium permanganate, Ziegler-Natta catalyst, titanium chloride, triethylaluminum, aluminum chloride, zirconium chloride, magnesium chloride, aluminum bromide, potassium permanganate, sodium persulfate, ammonium bromide, perchloric acid, hydrogen peroxide, sodium chlorate, nitric acid, silver nitrate, and sodium hypochlorite.
6. The method for preparing a 3D self-recovering flexible porous conductive material according to any one of claims 1 to 4, characterized in that: The soaking treatment time is 0.1 to 24 hours.
7. The method for preparing a 3D self-recovering flexible porous conductive material according to any one of claims 1 to 4, characterized in that: The monomer for preparing the conductive polymer includes any one of acetylene, aniline, pyrrole, fluorene, carbazole and thiophene.
8. The method for preparing a 3D self-recovering flexible porous conductive material according to any one of claims 1 to 4, characterized in that: The polymerization reaction time is 0.1 to 24 hours.
9. A 3D self-recovering flexible porous sensor, characterized in that: The 3D self-recovering flexible porous sensor is prepared by using a 3D self-recovering flexible porous conductive material, wherein the 3D self-recovering flexible porous conductive material is prepared by the preparation method of the 3D self-recovering flexible porous conductive material according to any one of claims 1 to 8.
10. The 3D self-recovering flexible porous sensor according to claim 9, characterized in that: The 3D self-recovering flexible porous sensor has triboelectric and piezoresistive dual sensing modes.